Straits settlements Blue Book (imports/exports) 1934-1935 vol.86-87 (Great Britain : Public Record Office, 1971)
Mengandungi sambungan kepada'Blue Book for the year 1934';'Blue Book for the year 1935';'Blue Book for the year 1936'.